Learning from Informal Settlements in Iran Models, Policies, Processes, and Outcomes - Arefi, Mahyar (Springer International Publishing, 2018)
This book explores the tenacity of Iran's informal settlements against the backdrop of the World Bank's USD 80 million loan for physical upgrading. Arefi seeks to identify and unravel the distinctive models, policies, processes, and outcomes associated with it, and explains why-despite obvious challenges-informal settlements remain popular in Iran, and also how understanding them in a broader theoretical context helps rectify existing redevelopment policies in order to develop more effective ones. .